The Enhancement of Learning Motivation by Using Blended Learning with Think-pair-share Technique for Prathomsueksa 4 Students of Dondoo School - Wichaiyo, Apichart; Teemueangsai, Sanit; Juntarasena, Ubonwan (Interdisciplinary Academic and Research Journal, 2023)
Enhancing achievement motivation is an important element that helps learners to persevere and determines their goals and academic outcomes. Motivation is the process by which a person is motivated by an intentional stimulus to act to achieve an objective, the learner becomes motivated, and teachers should motivate and build academic skills through teaching strategies that guide learners' learning methods. This research aims to 1) Study the promotion of motivation for academic achievement by managing blended learning with the think-pair-share technique. 2) to study the relationship between learning achievement and learning Achievement Motivation. 3) Study the student's satisfaction with learning. by managing blended learning with the Think-pair-share technique Procedure based (PAOR) The target group used in the research were 8 students in Prathom Suksa 4, Ban Don Du School. Under the Office of Maha Sarakham Primary Education Service Area 1 The research tool was a blended learning management plan using peer-to-peer technique. Motivation form for learning achievement Achievement test, annotated form, a behavioral observation form, and a satisfaction questionnaire. The statistics used in the research were mean, standard deviation, and correlation coefficient. The results of the research revealed that 1) promoting motivation for learning achievement. by managing blended learning with the think-pair-share technique. There are 5 steps, including the introduction to the lesson. teaching and problem-solving buddy step Group Work and Presentation and Summary and Assessment by providing a learning environment both in the classroom and online. 2) The motivation for learning achievement and learning achievement were positively correlated, and 3) Students are satisfied with the blended learning activities. with the technique of a partner who thinks at the highest level.